Genetic differentiation in populations of Exserohilum turcicum from maize and sorghum in South Africa. (3rd May 2018) - Nieuwoudt, A.; Human, M. P.; Craven, M.; Crampton, B. G.
Abstract : Exserohilum turcicum is the causal agent of northern leaf blight, a devastating foliar disease of maize and sorghum. Specificity of E .  turcicum to either maize or sorghum has been observed previously, but molecular evidence supporting host specialization is lacking. The aim of this study was to compare the genetic structure of E .  turcicum isolates collected from adjacent maize and sorghum fields in Delmas and Greytown in South Africa. In addition, the mode of reproduction of this pathogen was investigated. Isolates from maize ( N  = 62) and sorghum ( N  = 64) were screened with 12 microsatellite markers as well as a multiplex mating type PCR assay. No shared haplotypes were observed between isolates from different hosts, although shared haplotypes were detected between isolates from maize from Delmas and Greytown. Population structure and principal coordinate analyses revealed genetic differentiation between E .  turcicum isolates from maize and sorghum. Analysis of molecular variance indicated higher among‐population variation when comparing populations from different hosts, than comparing populations from different locations. Lack of shared haplotypes, high proportion of private alleles, greater among‐population variance between hosts than locations and significant pairwise population differentiation indicates genetic separation between isolates from maize and sorghum. The high haplotypic diversity in combination with unequal mating type ratios and significant linkage equilibrium indicates that both sexual and asexual reproduction contributes to the population genetic structure of E .  turcicum in South Africa.